DEVELOPMENT OF THE TECHNICAL AND IT LANGUAGE IN STUDENTS AS A COMPONENT OF THE POLISH EDUCATION SYSTEM - Waldemar, LIB (Trends in education, 2011)
The aim of each education system is to equip students with an indispensible set of knowledge and skills as well as rising in students and their attitudes such changes that may allow them to live proudly and develop national values in various aspects. These are material and nonmaterial values that support the development of culture in the society and nation. One of the most indispensible components of efficient functioning within the society, and, at the same time, developing its culture, especially the technical culture, relies on a language, with particular emphasis on the technical and IT language.
Keywords: education system; technical language; computer language.